Anticoagulation practices in adults with congenital heart disease and atrial arrhythmias in Switzerland. (22nd July 2018) - Arslani, Ketina; Notz, Lukas; Zurek, Marzena; Greutmann, Matthias; Schwerzmann, Markus; Bouchardy, Judith; Engel, Reto; Attenhofer Jost, Christine; Tobler, Daniel; ,
Abstract: Background: In adults with congenital heart disease (CHD) and atrial arrhythmias, recommendations for thromboprophylaxis are vague and evidence is lacking. We aimed to identify factors that influence decision‐making in daily practice. Methods: From the Swiss Adult Congenital HEart disease Registry (SACHER) we identified 241 patients with either atrial fibrillation (Afib) or atrial flutter/intraatrial reentrant tachycardia (Aflut/IART). The mode of anticoagulation was reviewed. Logistic regression models were used to assess factors that were associated with oral anticoagulation therapy. Results: Compared with patients with Aflut/IART, patients with Afib were older (51 ± 16.1 vs 37 ± 16 years, P < .001) and had a higher CHA2 DS2 ‐VASc ( P < .001) and HAS‐BLED scores ( P = .005). Patients with Afib were more likely on oral anticoagulation than patients with Aflut/IART (67% vs 43%, P < .001). In a multivariate logistic regression model, age [odds ratio (OR) 1.03 per year, 95%CI (1.01‐1.05), P = .019], atrial fibrillation [OR 2.75, 95%CI (1.30‐5.08), P = .007], non‐paroxysmal atrial arrhythmias [OR 5.33, 95%CI (2.21‐12.85)], CHA2 DS2 ‐VASc‐Score >1 [OR 2.93, 95%CI (1.87‐4.61), P < .001], and Fontan palliation [OR 17.5, 95%CI (5.57‐54.97), P < .001] were independently associated with oral anticoagulation treatment, whereas a HAS‐BLED score >1 was associated with absence of thromboprophylaxis [OR 0.32, 95%CI (0.17‐0.60), P < .001]. Conclusions: In this multicenter study, age, type, and duration of atrial arrhythmias, CHA2 DS2 ‐VASc and HAS‐BLED scores as well as a Fontan palliation had an impact on the use of thromboprophylaxis in adult CHD patients with atrial arrhythmias. In daily practice, anticoagulation strategies differ between patients with Afib and those with Aflut/IART. Prospective observational studies are necessary to clarify whether this attitude is justified.